When emotional valence modulates audiovisual integration. - Maiworm, M; Bellantoni, M; Spence, C; Röder, B (2012)
We constantly integrate the information that is available to our various senses. The extent to which the mechanisms of multisensory integration are subject to the influences of attention, emotion, and/or motivation is currently unknown. The "ventriloquist effect" is widely assumed to be an automatic crossmodal phenomenon, shifting the perceived location of an auditory stimulus toward a concurrently presented visual stimulus. In the present study, we examined whether audiovisual binding, as indicated by the magnitude of the ventriloquist effect, is influenced by threatening auditory stimuli presented prior to the ventriloquist experiment. Syllables spoken in a fearful voice were presented from one of eight loudspeakers, while syllables spoken in a neutral voice were presented from the other seven locations. Subsequently, participants had to localize pure tones while trying to ignore concurrent visual stimuli (both the auditory and the visual stimuli here were emotionally neutral). A reliable ventriloquist effect was observed. The emotional stimulus manipulation resulted in a reduction of the magnitude of the subsequently measured ventriloquist effect in both hemifields, as compared to a control group exposed to a similar attention-capturing, but nonemotional, manipulation. These results suggest that the emotional system is capable of influencing multisensory binding processes that have heretofore been considered automatic.